Tinjauan Kriminologi Terhadap Religas Tindak Pidana Perkosaan Oleh Anak di BAPAS Surakarta - Mutiara Nuqi Agustiana Putri; Rehnalemken Ginting (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The increasing number of rape crimes by child perpetrators is a serious problem that needs to be reviewed in depth, not only from a legal aspect, but also from a criminological perspective that takes into account the child's social, psychological and environmental background. The type of research used is empirical legal research with a descriptive-analytical approach. This study relies on primary data obtained through direct interviews with staff at the Surakarta Correctional Facility and literature reviews of relevant laws and scientific literature. The results of the study indicate that internal factors such as past trauma, psychological disorders, and lack of moral understanding, as well as external factors such as family and social environments and weak supervision, are triggers for children to commit rape. The role of BAPAS Surakarta is proven to be crucial in efforts to provide support, rehabilitation, and social reintegration for children following court rulings. This study is expected to contribute scientifically to efforts to prevent and address sexual violence by children, as well as provide input for the government and correctional institutions in developing policies based on a child protection approach.